2012
DOI: 10.2165/11630740-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Pharmacokinetics and Pharmacodynamics of Platelet Adenosine Diphosphate Receptor Antagonists and their Clinical Implications

Abstract: Over the last two decades or more, anti-platelet therapy has become established as a cornerstone in the treatment of patients with ischaemic cardiovascular disease, since such drugs effectively reduce arterial thrombotic events. The original agent used in this context was aspirin (acetylsalicylic acid) but, with the advent of adenosine diphosphate (ADP) receptor antagonists, the use of dual anti-platelet therapy has resulted in further improvement in cardiovascular outcomes when compared with aspirin alone. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
50
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 88 publications
0
50
0
Order By: Relevance
“…3,4 However, these agents are associated with higher risk of bleeding; are more costly; and differ in side effect profiles, drug interactions, contraindications, precautions for use, and dosing regimen. 5 When initiating ADP receptor inhibitors early during hospitalization for MI, information about the risk of recurrent thrombotic events, bleeding, patient adherence to medication, and affordability of drug may not be known. Given availability of several ADP receptor inhibitors, optimizing such factors during hospitalization by switching drug regimen may be a consideration for some patients.…”
mentioning
confidence: 99%
“…3,4 However, these agents are associated with higher risk of bleeding; are more costly; and differ in side effect profiles, drug interactions, contraindications, precautions for use, and dosing regimen. 5 When initiating ADP receptor inhibitors early during hospitalization for MI, information about the risk of recurrent thrombotic events, bleeding, patient adherence to medication, and affordability of drug may not be known. Given availability of several ADP receptor inhibitors, optimizing such factors during hospitalization by switching drug regimen may be a consideration for some patients.…”
mentioning
confidence: 99%
“…The first activation step is thought to be mediated largely by CYP2C19, CYP1A2, and CYP2B6, generating the intermediate metabolite 2-oxo-clopidogrel. This is followed by metabolism to the active metabolite, for which CYP3A, CYP2C19, CYP2B6, and CYP2C9 are involved (Kazui et al, 2010;Sangkuhl et al, 2010;Floyd et al, 2012). Genetic studies suggested a role for paroxonase 1 in the metabolic activation, but more recent studies have called this into question (see details below).…”
Section: A Clopidogrel Metabolismmentioning
confidence: 99%
“…[4][5][6][7][8][9] The thienopyridines clopidogrel and prasugrel are both prodrugs, which require metabolic conversion to form an active metabolite that irreversibly interacts with the P2Y 12 receptors of circulating platelets. 10 In contrast, ticagrelor is a reversible, non-competitive P2Y 12 antagonist (belonging to the cyto-pentyl-triazolo class of pyrimidines) interacting with the platelet receptors without metabolic conversion. [10][11][12] Due to the irreversible inhibition of the platelet P2Y 12 receptors by the active metabolites of clopidogrel and prasugrel, the formation of new platelets is required to recover platelet function.…”
Section: Introductionmentioning
confidence: 99%
“…10 In contrast, ticagrelor is a reversible, non-competitive P2Y 12 antagonist (belonging to the cyto-pentyl-triazolo class of pyrimidines) interacting with the platelet receptors without metabolic conversion. [10][11][12] Due to the irreversible inhibition of the platelet P2Y 12 receptors by the active metabolites of clopidogrel and prasugrel, the formation of new platelets is required to recover platelet function. 7,9 After ticagrelor treatment, recovery of platelet function is only determined by the elimination time of the drug (half-life of 8 h).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation